Meaning of work among cancer survivors: understanding critical paths to engagement - Nowacki, Emily, author; Byrne, Zinta, advisor; Howe, Adele, committee member; Vacha-Haase, Tammi, committee member (Colorado State University. Libraries, 2012)
Though connections between meaningful work and employee engagement exist, almost no empirical research has examined this relationship. Both meaningful work and employee engagement have important implications for employees and their employing organizations, especially in the context of stressful events or circumstances. The present study adds to our knowledge as to how the two constructs might relate to each other, by examining a population that was hypothesized as facing great barriers to becoming engaged: cancer survivors. Data for this study were collected by conducting semi-structured in-person and phone interviews with 12 employed cancer survivors. Interviews were coded and analyzed using grounded theory techniques to determine how meaningful work relates to employee engagement in situations of duress. The results suggest that participants reframed or reappraised the meanings they found at work in several ways that implied engagement (e.g., motivation to continue working or return to work). Based on the results of this initial grounded theory study, propositions are made for future investigation.
Keywords: cancer survivors; meaningful work; employee engagement